Energy Neutral Operation Method for Hybrid Energy Storage Integrated with Wind Farm Using C-Rate and Frequency Spectrum Analysis - (:unkn) unknown (My University, 2015)
In this thesis, the author describes various evaluation criteria, in particular the C-rate (charge/discharge-rate), of energy storage (ES) systems to explain the efficiency and technical benefits of battery-ultracapacitor hybrid energy storage (HES), and the technical characteristics of subsequently derived short-duration and long-duration type ES. In addition, for effective use of energy storage, a straightforward state of charge (SOC) correction method for energy neutral operation is proposed, and through a simple comparative example of ES operation, the effectiveness of HES in relation to simple ES is explained. A case is considered in which a hybrid ES controls the wind power ramp rate to comply with the regional system operator’s smoothing requirement, and an operation method is suggested through simulation. The simulation is carried out using a frequency spectrum analysis of wind power output profile and the C-rate of the hybrid storage system, and an energy neutral operation method for ES is proposed based on the simulated charging/discharging power sharing profile and SOC variations of the Li-battery and the ultracapacitor.
Keywords: Battery; Battery Storage; Energy Storage; ESS; Hybrid Energy Storage; Storage